A lightweight method for computing ball spin in real time - Cristina, Federico (2007)
The present paper poses a new method for computing the rotation of a ball in sport training situations, when the ball is approaching the goal line. The proposed method significantly reduces the hardware requirements associated to the capture, as well as the computational complexity necessary to obtain the results. The system's objective is to improve the player's technique and training methodology, and it is treated within the scope of the Institute's research line on signal and image processing areas. Experimental results will be presented using digitally generated images.